Synthesis and characterization of novel push-pull thiophene and thienylpyrrole derivatives functionalized with indanonedicyanovinyl acceptor moiety as efficient NLO-chromophores - Batista, Rosa Maria Ferreira (2011)
The synthesis and characterization of new chromophores with second-order nonlinearities containing thienylpyrrole 1a, 2a-b, bithiophene 3 and arylthiophene 4 as π-conjugated bridges and indanonedicyanovinyl acceptor group are reported. The effect of placing the acceptor group at thiophene or pyrrole rings on the optoelectronic properties was also evaluated for thienylpyrrole derivatives 1a and 2a-b. The linear optical properties (absorption and emission) for all compounds were evaluated in dioxane solutions. In addition, the hyperpolarizabilities β of chromophores 1-4 were measured using hyper-Rayleigh scattering in dioxane solutions and thermogravimetric analysis (TGA) was used to evaluate their thermal stability. The experimental results indicate that chromophores 1-4 are endowed with both excellent optical nonlinearities and high thermal stability making them interesting candidates for nonlinear optical (NLO) applications.